Commencement 2009 (Institutional Knowledge at Singapore Management University, 2009)
Vincent Ha Kwang Yuen receiving the valedictorian award from Deputy President Tan Chin Tiong at Singapore Management University's sixth commencement ceremony. Vincent graduates summa cum laude with a bachelor's degree in business management and a bachelor's degree in accountancy. The event was held at Suntec City Convention Centre on 11 July 2009.